Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification

MCM-41 supported phosphotungstic acid for the hydroxyalkylation of phenol to phenolphthalein - Jha, Ajay; Garade, Ajit C.; Mirajkar, Subhash P.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
A novel application of phosphotungstic acid, H3PW12O40 (PWA) supported on MCM-41 molecular sieve as a solid acid catalyst has been demonstrated for the synthesis of phenolphthalein by hydroxyalkylation of phenol and phthalic anhydride. PWA/MCM-41 (20%) showed the highest activity as compared to that of parent PWA and MCM-41 individually, due to the excellent dispersion of PWA on MCM-41 leading to the redistribution of Bronsted and Lewis acid sites on MCM-41. The effect of PWA loading on phthalic anhydride conversion and phenolphthalein selectivity was also studied. All these prepared catalysts were characterized by XRD, N-2 adsorption-desorption isotherm, pyridine-FTIR, and NH3-TPD. The effect of various reaction parameters, namely, mole ratios, catalyst concentration, temperature, reaction time, and percentage of PWA present in the catalysts on conversion and selectivity of products has been also investigated. The utility of 20% PWA/MCM-41 catalyst was established by its efficient activity for hydroxyalkylation of phenol and p-cresol with formaldehyde to the corresponding dihydroxydiarylmethane products.

Highly selective liquid-phase aerobic oxidation of vanillyl alcohol to vanillin on cobalt oxide (Co3O4) nanoparticles - Jha, Ajay; Rode, Chandrashekhar V. (New Journal of Chemistry, 2013)
Spinel Co3O4 nanoparticles prepared by solution phase method having particle size in the range of 12-20 nm exhibited excellent activity for the liquid-phase aerobic oxidation of vanillyl alcohol with 80% conversion and 98% selectivity to vanillin. Our catalyst could be reused three times without appreciable loss in activity. The catalytic activity of the Co3O4 nanoparticles was found to be similar to its homogenous precursor (cobalt acetate) and greater than the commercial Co3O4 oxide. The detailed characterization results of morphology, size and structure of the prepared Co3O4 nanoparticles obtained by XRD, FT-IR, H-2-TPR, HR-TEM and cyclic voltammetry technique were used to understand the roles of various Co species in directing the selectivity towards vanillin.

Magnetically separable single-site Ti-Fe3O4@MCM-41 catalyst for selective epoxidation of olefins - Jha, Ajay; Patil, Chetana R.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2013)
Magnetically separable Ti-Fe3O4@MCM-41 (Ti-MS) catalysts were prepared by postgrafting Ti with varying loading on mesoporous silica containing dispersed magnetite. The hexagonal structure of Ti-MS catalysts with a periodicity in the pores and a highly ordered hexagonal matrix was established by X-ray diffraction and transmission electron microscopy, while diffuse reflectance UV showed the isolated tetrahedral Ti species coordinated with O2-. From the Fourier transform infrared studies, the extent of Ti-O-Si linkage was found to increase with increase in Ti-loading from 1 to 5 wt %beyond which (10%), the intensity of Ti-O-Si band decreased due to the polymerization of the Ti on the silica surface. Silanol groups on the surface of silica interact with the precursor Ti((OPr)-Pr-i)(4) to give site isolated tetrahedral Ti-species responsible for complete selectivity to the epoxide in the epoxidation of cyclooctene. The magnetic property facilitated easy recovery of the catalyst for its successful eight recycles showing its stability under reaction conditions.

Metal cation-exchanged montmorillonite clay as catalysts for hydroxyalkylation reaction - Jha, Ajay; Garade, Ajit C.; Shirai, M.; Rode, C. V. (Applied Clay Science, 2013)
Several solid acid catalysts were prepared by exchanging metal cations such as Zn2+, Fe3+ and Al3+ with montmorillonite clay. Among these, Al-montmorillonite showed the highest acidity determined by the pyridine-IR as well as NH3-TPD methods. A systematic comparison of the performance of these catalysts along with parent montmorillonite was carried out for the hydroxyalkylation of p-cresol with formaldehyde to give 2, 2'-methylenebis (4-methyl phenol) (DAM). It was found that the activity of these catalysts was in accordance with the increase in acidity of parent montmorillonite after the exchange of cations in the order of Zn2+, Fe3+ and Al3+. The selectivity pattern was also influenced by the exchanged cations. Since Al-montmorillonite showed the highest conversion of 51% with 98% selectivity to DAM, the effects of various reaction parameters, namely, mole ratio, catalyst concentration, temperature, reaction time on conversion and selectivity pattern were also studied using the same catalyst This catalyst also showed an excellent stability as evidenced by its eight times reuse. (C) 2012 Published by Elsevier B.V.
Keywords: Cations-exchanged clay; Montmorillonite; NH3-TPD; Pyridine-IR

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol

Solvothermal synthesis of mesoporous manganese oxide with enhanced catalytic activity for veratryl alcohol oxidation - Jha, Ajay; Chandole, Tejansh; Pandya, Rajan; Roh, Hyun-Seog; Rode, Chandrashekhar V. (RSC Advances, 2014)
Catalyst activities of manganese and cobalt oxides prepared by solvothermal and co-precipitation methods were studied for veratryl alcohol oxidation. Manganese oxides showed higher activity performance than that of cobalt oxides irrespective of the method of preparation. The solvothermal method yielded mesoporous manganese oxide without using any template giving mixed phases of monoclinic Mn5O8 and hausmannite Mn3O4. The mesoporous manganese oxide exhibited excellent activity for liquid phase aerobic oxidation of veratryl alcohol under base free conditions, with 90% conversion and almost complete selectivity towards veratraldehyde. The detailed characterization results on morphology, size and composition of the prepared mesoporous manganese oxide obtained by XRD, XPS, H-2-TPR, N-2 adsorption-desorption isotherms, FESEM and HR-TEM techniques were used to understand the role of morphological and structural features in enhancement of the observed catalytic activity.

Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.

Mesoporous NiCu-CeO2 oxide catalysts for high-temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Jang, Won-Jun; Rode, Chandrashekhar V.; Roh, Hyun-Seog (RSC Advances, 2015)
Mesoporous NiCu-CeO2 oxide catalysts were synthesized by using the evaporation-induced self-assembly method applied to the high-temperature, water-gas shift reaction (HT-WGS) between 350 to 550 degrees C. Nickel and copper loadings on mesoporous ceria were tailored to achieve high activity and selectivity by suppressing methane formation in HT-WGS. Among the prepared catalysts, NiCu(1 : 4)-CeO2 exhibited the highest selectivity to CO2 and H-2 with 85% CO conversion at a very high GHSV of 83 665 h(-1). The higher activity of the catalysts was due to the mesoporous architecture, which provides more accessible active sites for the WGS reaction. Powder X-ray diffraction (XRD), small angle X-ray scattering (SAXS), N-2-adsorption/desorption isotherm, high-resolution transmission electron microscopy (HR-TEM), and H-2-temperature-programmed reduction (TPR) techniques were used to understand the role of mesoporosity and bimetallic composition of various NiCu-CeO2 oxides in enhancing catalytic activity for HT-WGS.

Reduced graphene oxide composite with oxidizable manganese/cobalt mixed oxide for p-cresol oxidation by using molecular oxygen - Jha, Ajay; Patil, Sagar H.; Solanki, Bhanu P.; Ribeiro, Ana P. C.; Castro, Carlos A. N.; Patil, Kashinath R.; Coronas, Alberto; Rode, Chandrashekhar V. (ChemPlusChem, 2015)
A composite of graphene oxide (GO) with mixed oxide (MnCo) was prepared by using a solvothermal method. During the synthesis, both the reduction of GO and growth of metal oxides took place simultaneously. The as-prepared composite material was highly selective for the liquid-phase oxidation of p-cresol to form p-hydroxybenzaldehyde in 71% yield within 1h. The composite material was characterised by SEM, X-ray photoelectron spectroscopy, high-resolution TEM and cyclic voltammetry (CV). A CV study revealed that the increase in the redox potential of the mixed oxide after being supported on GO, led to its higher activity of the catalyst for the oxidation reaction. The stability of the catalyst under the reaction conditions was studied by its successful reuse in three cycles.
Keywords: cyclic voltammetry; graphene; Oxidation; supported catalysts; transition metals

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Photoactive anthraquinone-based host-guest assembly for long-lived charge separation - Jha, Ajay; Mote, Kaustubh R.; Chandra, Suman; Madhu, Perunthiruthy K.; Dasgupta, Jyotishman (Journal of Physical Chemistry C, 2021)
Porous 2D covalent organic frameworks (COF) that are assembled axially through weak p-stacking interactions can provide reticular charge transport channels while playing host to kinetically stabilized reactive molecular redox states. Here we demonstrate a host-guest supramolecular charge transfer (CT) assembly using photoactive anthraquinone-based COF as an acceptor while incarcerating the electron donor N,N-dimethylaniline (DMA) inside it. Employing femtosecond broadband transient absorption spectroscopy in combination with electron paramagnetic resonance (EPR) studies, we show that the CT occurs rapidly within <110 fs after photoexcitation, subsequently leading to long-lived charge separation with 13% quantum efficiency at room temperature. The photoinduced EPR signature of the long-lived confined DMA cation radical confirms the disparate regions of charge localization while H-1-C-13 correlation experiments using solid-state NMR spectroscopy enumerate the packing of the amines inside the host-guest COF assembly. Our work demonstrates the potency of charge transport pathways in supramolecular assemblies for efficient charge separation which if optimally tuned should pave the way for COF-based photocatalytic reaction centers.